Adsorption of L-Histidine onto Functionalized Mesoporous SBA-15 Organosilicas - Monika Oszust; Karolina Gdula; Piotr Borowski; Andrzej Dąbrowski; Mariusz Barczak (Adsorption Science & Technology, 2015)
Adsorption of L-histidine (LH) over mesoporous SBA-15 silicas functionalized by amine-, thiol- and cyano-functional groups has been studied. These organosilicas have been synthesized by co-condensation of proper monomers in the presence of a template (Pluronic P-123), and characterized by elemental analysis, nitrogen adsorption, X-ray diffraction and transmission electron microscopy. The highest LH static adsorption capacity was observed for the cyano-functionalized sample [approximately 70 mg g −1 (450 mol g −1 )]; by contrast, pristine SBA-15 had a lowest adsorption capacity of approximately 25 mg g −1 (170 mol g −1 ).